The impact of corporate income tax on R&D of multinational entities: An impact analysis of separate taxation and CCCTB - Hulya Celebi; Sabina Hodžić (European Financial and Accounting Journal, 2017)
The significant contribution of R&D to economic development and sustainability has been shown by various studies. Therefore, governments offer different fiscal instruments to attract R&D, especially regarding multinational entities (MNEs). One of the fiscal instruments are tax incentives for R&D. Furthermore, the EU has been working on the switch from Separate Taxation (ST) to Common Consolidated Corporate Tax Base (CCCTB) for longer than a decade, which will lead to harmonized R&D tax allowances, however without harmonizing the tax rates. Hence, this study aims at analyzing how ST and CCCTB impact the location of MNEs' R&D activities, tax burden and countries' tax revenue through a case study. The results show that, under ST, tax jurisdictions can stimulate MNEs' R&D activities by means of attractive tax allowances and lower tax rates. Especially for high-tax countries, the tax allowances represent an important tool for attracting R&D activities. However, under CCCTB, the location of R&D activities additionally depends on the Formula Apportionment (FA) factors of the tax base, where the countries cannot exert a direct influence. Hence, the reduction of tax rates remains the only tool left to Member States, which can lead to revenue loss on the whole. Furthermore, the FA of the tax base under CCCTB mitigates the impact of any dislocation of R&D to a low-tax country, which, under ST, leads to larger tax savings of MNEs and its impact on jurisdictions' tax revenue is greater.
Keywords: H20; H25; O23; 650; CCCTB; Corporate income tax; Separate taxation; Tax incentives for R&D